Automated informed consent - Andreotta, Adam John; Lundgren, Björn (Big Data & Society, 2024)
Online privacy policies or terms and conditions ideally provide users with information about how their personal data are being used. The reality is that very few users read them: they are long, often hard to understand, and ubiquitous. The average internet user cannot realistically read and understand all aspects that apply to them and thus give informed consent to the companies who use their personal data. In this article, we provide a basic overview of a solution to the problem. We suggest that software could allow users to delegate the consent process and consent could thus be automated. The article investigates the practical feasibility of this idea. After suggesting that it is feasible, we develop some normative issues that we believe should be addressed before automated consent is implemented.
CRIS-Team Scopus Importer:2025-02-04
Keywords: automated consent; consent forms; ethics; Informed consent; privacy policy